Eficiência nutricional de nitrogênio e potássio no abacaxizeiro ‘Pérola’ em função das doses - Mata, Djair Alves da (2020)
Despite the increasing amount of information regarding mineral nutrition, little is known about the nutritional efficiency of pineapples. This work aimed to establish nutritional efficiency indexes for nitrogen and potassium in the pineapple ‘Pérola’, due to the application of increasing doses of these nutrients. The experiment was carried out under rainfed conditions, between December 2014 and June 2016, in Argissolo Vermelho-Amarelo in the municipality of Itapororoca, State of Paraíba. The experimental design was a randomized block with three replications. The treatments were arranged in a modified Experimental Plan Plan Puebla III, and resulted from the combination of five doses of N (50, 300, 500, 667 and 950 kg ha-1 - urea) and five doses of K (50, 300, 500, 667 and 950 kg ha-1 K2O - potassium sulfate). Slips of the type ‘young’ were used, planted in double rows, with spacing of 0.80 × 0.40 × 0.40 m. In sampling carried out after harvest, dry matter mass, N and K content and accumulation in the root, stem, leaf, seedling, fruit and total morphological parts were determined. The nutritional efficiency of the pineapple was evaluated through the utilization efficiencies (EFutz), conversion (EFcon), translocation (EFtra), absorption (EFabs) and recovery (EFrec). The doses of N and K influenced in an isolated and differentiated way the values of dry matter, contents and accumulations of these nutrients in the morphological parts of the pineapple (vegetative - root and stem; reproductive - seedling and fruit; and total), as well as the values of different calculated efficiencies. Increased doses of N and K increased EFabs and Eftra and reduced the Efutz, EFcon and EFrec of the respective nutrients. The EFrec of N and K decreased with the increase of the applied doses, going from 0.82 to 0.15 kg kg-1 and from 0.79 to 0.27 kg kg-1 with the increase of the doses of N and K2O of 1.2 to 22.8 g plant-1, respectively. The average recovery rate of N and K by the ‘Perola’ pineapple was 19.0 and 45.0%, respectively.